Pengelolaan Sistem Integrasi Aspirasi Pengaduan – Layanan Aspirasi dan Pengaduan Online Rakyat (SIAP-LAPOR!) dalam Mewujudkan Open government di Kabupaten Bojonegoro - Raden Rian Girianom; Nunik Retno (Journal of Politic and Government Studies, 2019)
Indonesia's participation in the application of Open government in 2011 is expected to improve the quality of public services, however, the ombudsman data in 2017 shows, that the most complained public service is the public services of local governments. Based on the follow-up of the Open government policy which was followed by several countries including Indonesia, the central government established an integrated complaints handling system called LAPOR (Layanan Aspirasi dan Pengaduan Online Rakyat) to improve the public services quality. Then, the complaints handling system is used by the Bojonegoro Regency government with the name SIAP-LAPOR (Sistem Integrasi Aspirasi Pengaduan – Layanan Aspirasi dan Pengaduan Online Rakyat). SIAP-LAPOR is an integrated complaint handling system where Bojonegoro district has become an Open government partnership pilot project in 2016.This research is purposed to find out the management of SIAP-LAPOR complaint handling system conducted by the Bojonegoro Regency Department of Communication and Informatics for the establishment of an open government in Bojonegoro Regency, it is assessed from the success element of e-government development where the results are being grand prerequisite of the three Open government principles including the Policy Principles, the Catalyst Principles and the Output Policy Principles (Output).This research uses descriptive qualitative methodology, and this research obtains information from interviews, observation, literature studies, and supporting documents. The result of this study indicates that the management of SIAP-LAPOR service has supported the three policy principles in the Open government grand theory. This is supported by the awards received by the Bojonegoro Regency Department of Communication and Informatics from Kemenpanrb (Ministry of Administrative and Bureaucratic Reform) for the top 10 management of complaints handling system in 2018, the availability of budget adequacy through the Regional Budget (APBD), and the human resources, as well as the completeness of information technology infrastructures. Some of the shortcomings in the findings of this research include the people who have not used SIAP-LAPOR services much, some people afraid to complaints and demand for responsiveness to the follow-up of OPD.Keyword : SIAP-LAPOR, Openness, Open government